2005
DOI: 10.1097/01.inf.0000190008.91534.b7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosed Tuberculosis During the Follow-up of a Cohort of Human Immunodeficiency Virus-Infected Children in Abidjan, C??te d??Ivoire

Abstract: The risk of tuberculosis among HIV-infected children in Côte d'Ivoire is strongly associated with the degree of immunodeficiency in HIV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…HIV-infected children, however, have a higher propensity for more extensive disease, more extrapulmonary disease and a higher rate of intracranial mass lesions [43,44 ,45]. Recurrent tuberculosis has been noted in 17 [43] and 10% [46] of patients, and this can be caused either by recurrence of the original infection or reinfection with a second strain of M. tuberculosis [46].…”
Section: Tuberculosis In Human Immunodeficiency Virus-infected Childrenmentioning
confidence: 98%
“…HIV-infected children, however, have a higher propensity for more extensive disease, more extrapulmonary disease and a higher rate of intracranial mass lesions [43,44 ,45]. Recurrent tuberculosis has been noted in 17 [43] and 10% [46] of patients, and this can be caused either by recurrence of the original infection or reinfection with a second strain of M. tuberculosis [46].…”
Section: Tuberculosis In Human Immunodeficiency Virus-infected Childrenmentioning
confidence: 98%
“…Adults with HIV disease have an increased incidence of pulmonary and extra pulmonary TB and also present with atypical pulmonary TB, less frequently being sputum smear-positive, and have a higher mortality rate [ 11,12]. A number of reports are available on the clinical manifestations and the outcome in small numbers of pediatric patients with HIV infection and TB [6,16,17,21]. In the most studies on HIV infection and TB in children from the developing countries, TB is not confirmed by culture.…”
Section: Introductionmentioning
confidence: 99%
“…uman immunodeficiency virus (HIV) infection in children increases the risk of developing active tuberculosis (TB) (1)(2)(3)(4) and is associated with a 2-to 6-foldgreater risk of dying from TB (3,(5)(6)(7)(8). The poor TB treatment outcome in HIV-infected children is in part due to ongoing immunosuppression and delay in initiation of antiretroviral therapy (9).…”
mentioning
confidence: 99%